Human face detection and recognition using contour generation and matching algorithm - Arulananth T.S; Baskar M.; Sateesh R. (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Face detection, monitoring of human face and recognition is a high-quality venture in safety, surveillance and regulation enforcement systems with greater accuracy. There are many motives at the back of in this trouble. Which include function of the human face; pose version, negative environmental conditions, terrible lightning and picture tilt etc,. So we must locate a few feasible solutions to clear up those issues by means of imposing a brand new system. Our proposed venture might be improving the issues on Face detection, monitoring of human face and recognition issues.